Thrombus Signal on T1-Weighted Black-Blood MR Predicts Outcomes of Catheter-Directed Thrombolysis in Acute Deep Vein Thrombosis - Huang, Chen; He, Xueping; Xie, Yueyuan; Chen, Hanwei; Ye, Yufeng; Sun, Yi; Dharmakumar, Rohan; Ryu, Robert K.; Li, Debiao; Xie, Guoxi; Fan, Zhaoyang (Thrombosis and Haemostasis, 2023)
Objectives Catheter-directed thrombolysis (CDT) is an effective therapy for acute deep vein thrombosis (DVT). However, predicting the CDT outcomes remains elusive. We hypothesized that the thrombus signal on T1-weighted black-blood magnetic resonance (MR) can provide insight into CDT outcomes in acute DVT patients.Methods A total of 117 patients with acute iliofemoral DVT were enrolled for T1-weighted black-blood MR before CDT in this prospective study. Based on the signal contrast between thrombus and adjacent muscle, patients were categorized into the iso-intense thrombus (Iso-IT), hyper-intense thrombus (Hyper-IT), and mixed iso-/hyper-intense thrombi (Mixed-IT) groups. Immediate treatment outcome (i.e., vein patency) and long-term treatment outcome (i.e., the incidence rate of postthrombotic syndrome) were accessed by the same expert. Histological analysis and iron quantification were performed on thrombus samples to characterize the content of fibrin, collagen, and the ratio of Fe3+ to total iron.Results Compared to Mixed-IT and Hyper-IT groups, the Iso-IT group had the best lytic effect (90.5 ± 1.6% vs. 78.4 ± 2.6% vs. 46.5 ± 3.3%, p < 0.001), lowest bleeding ratio (0.0 vs. 11.8 vs. 13.3, p < 0.001), and the lowest incidence rate of postthrombotic syndrome on 24 months (3.6 vs. 18.4 vs. 63.4%, p < 0.001) following CDT. The Iso-IT group had a significantly lower ratio of Fe3+ to total iron (93.1 ± 3.2% vs. 97.2 ± 2.1%, p = 0.034) and a higher content of fibrin (12.5 ± 5.3% vs. 4.76 ± 3.18%, p = 0.023) than Hyper-IT.Conclusion Thrombus signal characteristics on T1-weighted black-blood MR is associated with CDT outcomes and possesses potential to serve as a noninvasive approach to guide treatment decision making in acute DVT patients.Key Points
Keywords: deep vein thrombosis; magnetic resonance imaging; thrombolytic treatment; postthrombotic syndrome